84.7k views
7 votes
Evaluate the expression for d = 4, f = –3, and g = –12.

fg − d + f = ?

2 Answers

8 votes

Answer:29

Explanation:

[-3 ✖ -12] ➖ 4 ➕ 3

♒36 ➖ 7

♒ 29.✔

I hope i helped you

User Johnykes
by
5.3k points
12 votes

d= fgf+g-F

Explanation:

F = fg f + g - d solve the equation for d

Solve for d means we need to get 'd' alone

To get 'd' alone we need to move all the remaining terms to the other side

F = fg f + g - d

First we subtract fgf on both sides

F - fg f = g - d

Now we subtract g on both sides

F - fg f - g = - d

now divide all the term by -1, so sign changes for all terms

-F + fgf +g = d

so d= fgf+g-F

User John Breen
by
5.1k points